A new parameterization for ice cloud optical properties used in BCC-RAD and its radiative impact. (January 2015) - Zhang, Hua; Chen, Qi; Xie, Bing
Abstract: A new parameterization of the solar and infrared optical properties of ice clouds that considers the multiple habits of ice particles was developed on the basis of a prescribed dataset. First, the fitting formulae of the bulk extinction coefficient, single-scatter albedo, asymmetry factor, and δ-function forward-peak factor at the given 65 wavelengths as a function of effective radius were created for common scenarios, which consider a greater number of wavelengths and are more accurate than those used previously. Then, the band-averaged volume extinction and absorption coefficients, asymmetry factor and forward-peak factor of ice cloud were derived for the BCC-RAD (Beijing Climate Center radiative transfer model) using a parameter reference table. Finally, the newly developed and the original schemes in the BCC-RAD and the commonly used Fu Scheme of ice cloud were all applied to the BCC-RAD. Their influences on radiation calculations were compared using the mid-latitude summer atmospheric profile with ice clouds under no-aerosol conditions, and produced a maximum difference of approximately 30.0 W/m 2 for the radiative flux, and 4.0 K/d for the heating rate. Additionally, a sensitivity test was performed to investigate the impact of the ice crystal density on radiation calculations using the three schemes. The results showed that the maximum difference was 68.1 W/m 2 for the shortwave downward radiative flux (for the case of perpendicular solar insolation), and 4.2 K/d for the longwave heating rate, indicating that the ice crystal density exerts a significant effect on radiation calculations for a cloudy atmosphere. Highlights: A new parameterization of the radiative properties of ice cloud was obtained. More accurate fitting formulae of them were created for common scenarios. The band-averaged of them were derived for our radiation model of BCC-RAD. We found that there exist large differences of results among different ice schemes. We found that ice crystal density plays an important role in radiation calculations.